1996
DOI: 10.1089/hum.1996.7.9-1103
|View full text |Cite
|
Sign up to set email alerts
|

Gene Targeting to the Centromeric DNA of a Human Minichromosome

Abstract: A human supernumerary minichromosome (MC), previously identified as a derivative of chromosome 9, has been introduced into Chinese hamster ovary (CHO) cells by means of cell fusion. A hybrid clone containing the MC as the only free human chromosome was isolated. A selectable marker gene (neo) inserted into a yeast artificial chromosome (YAC) has been successfully targeted to the MC centromeric DNA via co-transfection with chromosome-9-specific alpha satellite DNA. In situ hybridization and Southern blotting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…This can be explained by the presence of an active centromere. Several studies using linear human minichromosomes already showed that these segregated properly in human or hamster cells in the absence of selection (Farr et al 1995;Raimondi et al 1996;Harrington et al 1997;Ikeno et al 1998). There is some evidence, however, that the copy number of smaller minichromosomes (2.4 Mb) is more variable in human and hamster cell lines (Mills et al 1999).…”
Section: Discussion Mitotic Stability Of the Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the presence of an active centromere. Several studies using linear human minichromosomes already showed that these segregated properly in human or hamster cells in the absence of selection (Farr et al 1995;Raimondi et al 1996;Harrington et al 1997;Ikeno et al 1998). There is some evidence, however, that the copy number of smaller minichromosomes (2.4 Mb) is more variable in human and hamster cell lines (Mills et al 1999).…”
Section: Discussion Mitotic Stability Of the Hcvmentioning
confidence: 99%
“…Minichromosomes (all containing ␣ satellite repeats) of less than 2.5 Mb, thus, have been created. Finally, several authors explored the possibility of using naturally occurring minichromosomes (Raimondi et al 1996;Guiducci et al 1999).…”
mentioning
confidence: 99%
“…The labeled probes were resuspended in hybridization buffer (50% formamide, 10% Dextran sulfate, 1ϫ Denhardt's solution, 0.1% SDS, 40 mM Na 2 HPO 4 , pH 6.8, and 2ϫ SSC) at a final concentration of 5 g/ml and they were denatured at 70°C for 10 min. FISH on metaphase spreads was carried out essentially as previously reported (Raimondi et al, 1996). For FISH analysis on interphase heat-shocked HeLa cells, cells were rinsed with PBS and fixed in 4% formaldehyde for 15 min at room temperature.…”
Section: Fishmentioning
confidence: 99%
“…To confirm this conclusion, we took advantage of the fact that a human supernumerary mini-chromosome spanning the 9p13-q13 region had been previously characterized in our laboratory (Raimondi et al, 1991). MCH cells containing a single mini-chromosome as the only human chromosome (Raimondi et al, 1996) were therefore challenged for the ability to form stress bodies after heat shock. As hamsterϾhuman hybrid were heat shocked at 42°C for 1 h and after 1 h of recovery at 37°C, were fixed with formaldehyde, stained with the EDTA technique, and analyzed in electron microscopy.…”
Section: Stress-induced Snbs Colocalize With the Pericentromeric Hetementioning
confidence: 99%
“…The existence of spontaneously arising or radiation-induced human marker chromosomes offers an alternative starting point for deriving a chromosomebased vector system. [11][12][13][14][15][16][17] A further chromosome engineering technology under development relies upon integration of exogenous DNA into the centromere region of a host mouse or human chromosome. Amplification of DNA at the integration site can result in chromosome breakage events, producing new large chromosomes typically in the 60-400 Mb size range.…”
Section: Introductionmentioning
confidence: 99%